MO297: Acute Kidney Injury Among COVID-19 Positive Patients is Associated With Higher Mortality: Single Center Experience. (3rd May 2022) - Ashry Ahmed Gheith, Osama; Maher Nagib, Ayman; Elserwy, Nabil; Abbas, Ahmad; Elsawi, Islam S; Nair, Prasad; Khalid, Mahmoud; Hammad, Mohamed; Fayyad, Zohair; Atta, Ahmed; Mostafa, Ahmed; Deraz, Ahmed; et al.
Abstract: BACKGROUND AND AIMS: Despite the lungs are the major targets of COVID-19, other organs such as the kidneys are also affected. Renal complications of COVID-19 are not yet well studied. We aimed to study the prevalence of acute kidney injury (AKI) among positive COVID-19 cases that were managed in the intensive care unit (ICU) in a single isolation hospital during the pandemic, and to explore its impact on patient outcome. METHOD: This retrospective study included 616 patients with COVID-19 who were managed in the ICU in a single isolation hospital in Kuwait during the pandemic, from February to December 2020. AKI was defined according to the serum creatinine criteria in the Kidney Disease: Improving Global Outcomes (KDIGO) guidelines. Of the 616 patients, 40.2% developed AKI (group 1, n  = 248) and were compared with the patients without AKI (group 2, n  = 368). RESULTS: Most of cases in the two groups were males (73% versus 70.7%), aged (60.8 ± 14 versus 51.7 ± 16 years), respectively. The two groups were comparable regarding chronic kidney disease (2% versus 0.8%) and chronic pulmonary disease. Other factors were significantly predominating among group 1 as diabetes mellitus (63.7 versus 40.5%), hypertension (74.2% versus 40.5%) and ischemic heart disease (26.2% versus 12.5%) ( P  < .05). Fever, cough, shortness of breath and dehydration were significantly more frequent presentations among patients of group 1, and had radiological findings that were synchronized with COVID-19 (89.5% versus 50.8%) ( P  < .05). Moreover, sepsis, volume depletion, shock, arrhythmias and ARDS predominated among the AKI group ( P  < .05). The number of cases who were managed by therapeutic anticoagulation was significantly higher in AKI patients (89.9% versus 51.9%); also, cases who received supportive vasopressors and convalescent plasma transfusion as well as steroid were significantly higher in the same group ( P  < .05). Other therapeutic modalities such as antivirals, tocilizumab and hydroxychloroquine were comparable in both groups. We found that acute respiratory failure requiring mechanical ventilation was significant among the AKI group (66.8% versus 29.4%), and the overall mortality rate was significantly higher in the same group (62.5% versus 32.8%). CONCLUSION: The prevalence of AKI in patients with COVID-19 was 40.2%, and it was associated with poor prognosis among ICU COVID-19 positive cases.